2016
DOI: 10.1002/stem.2473
|View full text |Cite
|
Sign up to set email alerts
|

Fascin Is Critical for the Maintenance of Breast Cancer Stem Cell Pool Predominantly via the Activation of the Notch Self-Renewal Pathway

Abstract: An emerging dogma shows that tumors are initiated and maintained by a subpopulation of cancer cells that hijack some stem cell features and thus referred to as "cancer stem cells" (CSCs). The exact mechanism that regulates the maintenance of CSC pool remains largely unknown. Fascin is an actin-bundling protein that we have previously demonstrated to be a major regulator of breast cancer chemoresistance and metastasis, two cardinal features of CSCs. Here, we manipulated fascin expression in breast cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 56 publications
6
63
0
Order By: Relevance
“…10 Spontaneous or chemotherapy-mediated cell apoptosis was analyzed using Annexin V staining kit (Life Technologies) as previously described. 10 Spontaneous or chemotherapy-mediated cell apoptosis was analyzed using Annexin V staining kit (Life Technologies) as previously described.…”
Section: Flow Cytometry and Cell Sortingmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Spontaneous or chemotherapy-mediated cell apoptosis was analyzed using Annexin V staining kit (Life Technologies) as previously described. 10 Spontaneous or chemotherapy-mediated cell apoptosis was analyzed using Annexin V staining kit (Life Technologies) as previously described.…”
Section: Flow Cytometry and Cell Sortingmentioning
confidence: 99%
“…10 Adhesion assay A plate (96-well) was coated overnight at 4 C with different concentration of ECM substrates including; Matrigel (Corning), 40 μg of Collagen IV (Millipore), 5 μg of Fibronectin (Millipore) and 60 μg of Laminin (Millipore) as previously described. Fascin-positive or -negative cells that express or lack ITGB1 were seeded at 100 cell/well in 3 ml of complete DMEM media for 10-12 days at 37 ο C, 5% CO 2 humidified incubator.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Barnawi et al reported that fascin (an actin-bundling protein) effectively regulates breast CSCs at least partially through Notch pathway [78]. Fascin knockdown significantly reduced breast stem cell-like phenotype (downregulation of stem cell pluripotent genes such as Oct4, Nanog, Sox2, and Klf4), and the cells became less competent in forming colonies and tumorspheres.…”
Section: Signaling Pathways In Cscsmentioning
confidence: 99%
“…Fascin knockdown significantly reduced breast stem cell-like phenotype (downregulation of stem cell pluripotent genes such as Oct4, Nanog, Sox2, and Klf4), and the cells became less competent in forming colonies and tumorspheres. Conversely, activation of Notch signaling induced the relevant downstream targets predominantly in the fascin-positive cells, and fascin-positive CSCs showed stronger tumorigenesis [78]. In another study, immunohistochemical analysis of 115 breast tumor tissues from primary lesions was performed, and results showed that Notch positive tissues were significantly associated with a CSC marker aldehyde dehydrogenase 1 family member A1 levels [79].…”
Section: Signaling Pathways In Cscsmentioning
confidence: 99%